1972
DOI: 10.1007/bf01911930
|View full text |Cite
|
Sign up to set email alerts
|

Determination of water content by means of the Derivatograph

Abstract: The determination of water content by means of the Derivatograph is treated in the paper. The determination of water in analytical precipitates, various pharmaceutical products, biological substances, the products of food industry is treated on the basis of some practical examples. The applicability of the Derivatograph for determining the adsorption capacity of industrial adsorbents, the hydration conditions of cement, the system Ca3A--CaSO4 9 HyO and the rehydrability of clay minerals is demonstrated. The al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

1973
1973
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…Figure 1 presents the thermal distribution of hydrated copper sulphate under quasi-isothermal conditions. Crystal water is seen to be evolved from the sample in a manner dependent on temperature [1][2][3][4][5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 presents the thermal distribution of hydrated copper sulphate under quasi-isothermal conditions. Crystal water is seen to be evolved from the sample in a manner dependent on temperature [1][2][3][4][5][6][7][8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…adsorption capacity or porous structure) [1][2][3]. The results of measurements of liquid adsorption and desorption from the gaseous phase and the heats of processes taking place on silica gel surfaces with a derivatograph are presented in [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Simon [1] described the applicability of the derivatograph for determination of the adsorption capacity of industrial adsorbents. Das et al [3] recently used the complex method for studies on the change of amorphous silica into crystobalite.…”
mentioning
confidence: 99%
“…Studies have shown that during reaction (1), in addition to changes in the adsorption properties of the silica gel [4,11 ], its texture and skeleton structure may also undergo modification [9,12].…”
mentioning
confidence: 99%
“…The derivatograph has been used to determine the amount of moisture [10], and also indirectly for the estimation of water adsorption isotherms on solids [11]. The samples investigated were placed in desiccators over sulphuric acid solutions of suitable concentration, i.e.…”
mentioning
confidence: 99%